واقع ممارسات إدارة المواهب في شركة كوندور الكترونيكس من وجهة نظر العاملين في إدارة الموارد البشرية - عفانة, أحمد; عثماني, مصطفى (جامعة الوادي - University of Eloued, 2021)
This study aimed to know the level of talent management practices in Condor Electronics Corporation - Bordj Bou Arreridj-. Using the analytical descriptive approach and the intentional sampling method to achieve the goal of the study. The sample targeted a number (50) of staff and administrators working in the Human Resources Directorate and some of its sections in the company'svarious production units. The questionnaire was used as the main tool for the study and the use of the statisticalanalysis program spss v25. This study findsseveral conclusions the most prominent of that the level of all talent management practices in Condor Electronics is high, as well as the practice of performance management in the first place among the talent management practices, and in light of the results, this study essentially suggested the need to strengthen talent management as a permanent organizational culture.
The reality of talent management practices at Condor Electronics from the perspective of human resources management workers
مقال
Keywords: تخطيط المواهب ; استقطاب المواهب ; تطوير المواهب ; إدارة الأداء ; استبقاء المواهب